Associations of Perception towards Doctors, Nurses, and Facilities with Perceived Quality and Patient Satisfaction on Inpatient Care at Nabire Hospital Papua - Agustina Utii; Bhisma Murti; Yulia Lanti Retno Dewi (Journal of Health Policy and Management, 2020)
Background: The government's efforts to maintain and improve the highest health status with all resources in the health sector, including personnel, funds, facilities, pharmacy, medical devices, and technology, provide quality health care. Community satisfaction as the service receiver is a comparison between the services received and the services expected. This study aimed to examine associations of perception towards doctors, nurses, and facilities with perceived quality and patient satisfaction on inpatient care at Nabire Hospital Papua.Subjects and Method: A cross-sectional study was conducted at Nabire Hospital, Papua, Indonesia, from March to May 2020. A sample of 207 inpatients was selected by stratified random sampling based on the type of inpatient class I, II, and III.Results: Inpatient satisfaction was affected by age <50 years (b= -0.36; 95% CI= -1.63 to 0.91; p=0.579), type of non-BPJS insurance (b= 0.19; 95% CI= -0.80 to 1.19 p= 0.697), length of stay <7 days (b= -2.39; 95%CI= -3.86 to -0.92; p <0.001), patients’ perception towards adequate inpatient facilities (b=3.11; 95%CI=2.13 to 4.07; p <0.001), good quality of inpatient care (b= 2.74; 95% CI= 1.74 to 3.72; p <0.001). The good quality of inpatient care was affected by male sex (b= 0.91; 95% CI= 0.10 to 1.72; p= 0.028), age <50 years (b= -0.24; 95% CI= -1.26 to 0.78; p= 0.644), type of BPJS insurance (b= 0.41; 95% CI= -1.22 to 0.39; p= 0.318), perception towards adequate facilities (b= 1.85; 95% CI= 1.04 to 2.65; p<0.001), good perception towards nurses (b= 2.18; 95%CI= 1.04 to 3.33; p <0.001), and good perception towards doctors (b= 1.68; 95% CI= 0.89 to 2.47; p <0.001). The good perception towards doctors was affected by the education of patients ≥Senior High School (b= 1.16; 95% CI= 0.31 to 1.83; p= 0.005).Conclusion: Inpatient satisfaction is affected by age <50 years, type of non-BPJS insurance, length of stay <7 days, perception towards adequate facilities, and good quality of inpatient care.Keywords: Quality, satisfaction, inpatient, path analysisCorrespondence: Agustina Utii. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: agustinautii1@gmail.com. Mobile: 081240051451.Journal of Health Policy and Management (2020), 05(03): 215-223https://doi.org/10.26911/thejhpm.2020.05.03.07